MENINGKATKAN KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MASALAH MATEMATIS SISWA SD KELAS V MELALUI PENDEKATAN MATEMATIKA REALISTIK - Fitriani, Kartika; Maulana, Maulana (Mimbar Sekolah Dasar, 2016)
This research is conducted to all fifth-grade elementary school students throughout the Subdistrict Conggeang that included higher group. The research result indicates that the realistic mathematics education and conventional approach give different effect to students’ mathematical understanding and problem-solving abilities. The effect to mathematical understanding and problem-solving ability in experiment class is better than the control one. The effect of realistic mathematics education to the higher, middle, and lower achievement students group is different too. Higher group gets a bigger effect than others. There is a positive correlation between mathematical understanding and problem-solving abilities, which its contribution is 95, 9%.Keywords: realistic mathematics education, mathematical understanding ability, mathematical problem solving ability.